1980
DOI: 10.1177/001316448004000447
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Predictive Validities of Selected Academic Tests of the American College Test (Act) Assessment Program and the Descriptive Tests of Language Skills for College Freshmen in a Basic Skills Program

Abstract: A comparative evaluation was made of the ability of the four Academic Tests of the American College Test (ACT) Assessment Program and the Descriptive Tests of Language Skills (DTLS) to predict course grades and freshman grade-point average for 496 students enrolled in a basic skills program at a large four-year midwestern university. Multiple regression analyses indicated that performance in basic skills courses, notably reading and writing, can be predicted equally well by a subset of the Academic Tests of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…Once again, the results received with this particular sample contradict those found in the literature(Kirkland & Hollandsworth, 1979;Snowman et al, 1980; Ya- magishi & Gillmore, 1980).…”
contrasting
confidence: 72%
“…Once again, the results received with this particular sample contradict those found in the literature(Kirkland & Hollandsworth, 1979;Snowman et al, 1980; Ya- magishi & Gillmore, 1980).…”
contrasting
confidence: 72%
“…Stumpf and Stanley (2002) found that ACT scores show a .70 correlation with college graduation rates. In addition, ACT scores have been shown to correlate with college GPA from .54 to .63, and the ACT math subtest correlates with math GPA from .48 to .64 (Koretz & Berends, 2001;Pettijohn, 1995;Sibert & Ayers, 1989;Snowman, Leitner, Snyder, & Lockhart, 1980). Composite ACT scores are generally better at predicting college GPA than is high school GPA, especially at high levels of ability (Noble & Sawyer, 2002).…”
mentioning
confidence: 99%